Short Communication A Novel Diagnostic Test for Pre-Eclampsia: Congo Red Dot Test - Anwar, Haleema (International Journal of Pathology, 2022)
Preeclampsia(PE) is a disorder of pregnancy characterized with hypertension (after week 20), proteinuria and affected systemic systems. Preeclampsia is a leading cause of maternal mortality worldwide and it is of importance to come up with economically reasonable biomarkers to predict it. Thus, Urine congophillia in PE has been studied. Misfolded proteins are detected in the urine and serum of such patients. These proteins bind easily to various dyes especially Congo red dye, which is the basis of this diagnostic test. The article will highlight the pathology of preeclampsia, type of protein in the urine of preeclamptic patients and Congo red test for preeclampsia.